High frequency of Nichols-like strains and increased levels of macrolide resistance in Treponema pallidum in clinical samples from Buenos Aires, Argentina - Morando, Nicolas; Vrbová, Eliška; Melgar, Asunta; Rabinovich, Roberto Daniel; Šmajs, David; Pando, María A (Scientific reports, 2022)
Globally, 94% of Treponema pallidum subsp. pallidum (TPA) clinical strains belong to the SS14-like group and 6% to the Nichols-like group, with a prevalence of macrolide resistance of 90%. Our goal was to determine whether local TPA strain distribution and macrolide resistance frequency have changed significantly since our last report, which revealed that Buenos Aires had a high frequency of Nichols-like strains (27%) and low levels of macrolide resistance (14%). Swab samples from patients with suspected syphilis were collected during 2015-2019 and loci TP0136, TP0548, TP0705 were sequenced in order to perform multilocus sequence typing. Strains were classified as Nichols-like or SS14-like. The presence of macrolide resistance-associated mutations was determined by examination of the 23S rDNA gene sequence. Of 46 typeable samples, 37% were classified as Nichols-like and 63% as SS14-like. Macrolide resistance prevalence was 45.7%. Seven allelic profiles were found, five were SS14-like and two were Nichols-like. The frequency of Nichols-like strains increased between studies (26.8% vs. 37%, p = 0.36). A dramatic increase was found in the frequency of macrolide resistant strains between studies (14.3% vs. 45.7%, p = 0.005). Our results are in agreement with international trends and underscore the need to pursue further TPA molecular typing studies in South America.
Keywords: antibakteriální látky; Treponema; Anti-Bacterial Agents; lidé; Argentina; DNA, Ribosomal; Macrolides; makrolidy; Drug Resistance, Bacterial; Multilocus Sequence Typing; Treponemal Infections; Humans; multilokusová sekvenční typizace; ribozomální DNA; Treponema pallidum; infekce bakteriemi rodu Treponema; bakteriální léková rezistence